THE EFFECTIVE METHODS AND MEDIAS USED IN HEALTH PROMOTION ABOUT ADOLESCENT HEALTH PRODUCTION - Ida Puspita Sari (Universitas Airlangga, 2023)
Introduction: Adolescence is a period that determines the pattern of formation of later health status in adulthood. The phase toward the final adolescent will require a lot of effort to be more maximal. It’s because when starting adolescence, someone psyche becomes unstable, so it’s need for assistance. Risk behavior generally starts in this period. Aims: To summarize the scattered research on adolescent health to gain a more complete and varies illustration of the methods and media that have been used in adolescent health promotion and its effectiveness. Methods: The method used in writing this article is the literature review. The articles includes several books, journals, and health profile books issued by the agency. Results: The methods and media used to carry out health promotion in adolescents must be based on analysis of the situation. In addition, it also looks at the age patterns of target so that they can be interested. The method of deliver greatly influences the target's response to information. A more effective method is a method which combines many human senses. It also necessary to insert an atmosphere breaker for methods that can make boredom if done over a long time and monotonous. Conclusion: Social media is suitable to be used as an intermediary for delivering information in accordance with the frequency of teenagers accessing social media on a daily basis. Peer education and the involvement of education on reproductive health in the curriculum is a method that can improve adolescent understanding of reproductive health.